The genus Baetodes Needham & Murphy (Ephemeroptera-Baetidae) in Colombia, with the description of twelve new species - Jimenez, Luis Gonzalo Salinas; Salles, Frederico Falcão (Zootaxa, 2026)
Baetodes Needham & Murphy is one of the most diverse genera of Baetidae with 51 species distributed from the United States to Argentina. In Colombia, seven species have been recorded; here, based on the description of new species, we increase the number to 19. Diagnoses of all of them are presented. Twelve new species are described based on nymphs (B. acanthosternus sp. nov., B. caldensis sp. nov., B. colobranchius sp. nov., B. colombiensis sp. nov., B. dicyrtus sp. nov., B. huilensis sp. nov., B. ironmaiden sp. nov., B. notospinae sp. nov., B. proterochaetus sp. nov., B. speciosus sp. nov., B. unbranchomerus sp. nov., and B. wiphala sp. nov.). An identification key is developed for the species from Colombia and new characters for nymphs of Baetodes are proposed.